Primaquine for Plasmodium vivax radical cure: What we do not know and why it matters. (April 2021) - Popovici, Jean; Tebben, Kieran; Witkowski, Benoit; Serre, David
Abstract: Plasmodium vivax radical cure requires the administration of a blood schizonticide for killing blood-stage parasites and the addition of a drug able to kill hypnozoites, the dormant parasite stages residing in the liver of infected patients. All drugs used clinically for killing hypnozoites are 8-aminoquinolines and among them, primaquine has been at the forefront of P. vivax case management for decades. We discuss here the possible factors that could lead to the emergence and selection of P. vivax primaquine resistant parasites and emphasize on how a better understanding of the mechanisms underlying primaquine treatment and hypnozoite biology is needed to prevent this catastrophic scenario from happening. Graphical abstract: Image 1